THE CREATIVE THINKING -THE CREATIVE PROCESS AND THE TEACHING OF COLORS (Revista Apotheke, 2022)
This article reports an experience in learning about colors held inthe subject entitled Color Funtamentals of Fashion Design course of  CEART/UDESC in 2012. The challenge established in the subjectwas teaching the basic concepts about colors, its characteristics, uses, chromatic circle and harmonic schemes. In the subject’s beginning,the tasks and the theoretical framework that involved the creativeprocess and the teaching of colors through exercises developed in class were established. This text shows a brief presentation of the work developed during the semester.
Keywords: Crativity; Color; Teaching